(untitled) (Journal of Human Sciences, 2018)
Poet of " Al-mawakib" is human poetic experience and its meaning summarized in first and last stanza. Gibran stand between duality of Good and Evil, Will and looting of the will in front of density and using new method and special style to transfer the experience. He depend on two poetic meters to design the poem in two different rhythms in many dialogical scenes to share intercultural dialogue and philosophical debate, which presented in two voices: conflict in Gibran’s soul between the Good in human soul , and what the poet sees in life. The poet allows to himself moving from idea to other and increasing saying field in the one idea by using some language expressions and structures in its metaphorical meaning, and other technical meaning such: contrast, formations and discrepancy. Therefore, he found two texts inside one and each text presents society and each text has its tone, music and special rhythm.